2021
DOI: 10.1038/s41467-021-24876-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-induced senescence in hematopoietic progenitors features myeloid restricted hematopoiesis, chronic inflammation and histiocytosis

Abstract: Activating mutations in the BRAF-MAPK pathway have been reported in histiocytoses, hematological inflammatory neoplasms characterized by multi-organ dissemination of pro-inflammatory myeloid cells. Here, we generate a humanized mouse model of transplantation of human hematopoietic stem and progenitor cells (HSPCs) expressing the activated form of BRAF (BRAFV600E). All mice transplanted with BRAFV600E-expressing HSPCs succumb to bone marrow failure, displaying myeloid-restricted hematopoiesis and multi-organ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
(35 reference statements)
2
23
0
Order By: Relevance
“…p16 expression by large pale histiocytes of RDD could be considered as a senescence marker, like what has been demonstrated in ECD and LCH 35 , 36 , 43 , 44 . Activating mutations in the BRAF-MAPK pathway induces a senescence program (oncogene induced senescence, OIS), characterized by a reprogramming of mutated cells with a DNA damage response activation and a senescence-associated secretory phenotype – SASP –, affecting non-mutated bystander cells.…”
Section: Morphology Immunophenotype and Molecular Alterations In Rddsupporting
confidence: 57%
“…p16 expression by large pale histiocytes of RDD could be considered as a senescence marker, like what has been demonstrated in ECD and LCH 35 , 36 , 43 , 44 . Activating mutations in the BRAF-MAPK pathway induces a senescence program (oncogene induced senescence, OIS), characterized by a reprogramming of mutated cells with a DNA damage response activation and a senescence-associated secretory phenotype – SASP –, affecting non-mutated bystander cells.…”
Section: Morphology Immunophenotype and Molecular Alterations In Rddsupporting
confidence: 57%
“…reported that mesenchymal stem/progenitor cells in middle-aged mice have an increased senescent phenotype and that NSAID treatment can improve fracture healing in middle-aged mice ( 9 ). However, emerging evidence also indicates that senescence is an upstream source of inflammatory factors ( 37 , 43 ). Biavasco et al.…”
Section: Discussionmentioning
confidence: 99%
“…Biavasco et al. reported that oncogene-activated senescence of human hematopoietic stem and progenitor cells promotes systemic inflammation by secreting TNFα ( 37 , 43 ). In the present study, we observed that treatment of CaMPCs with SC CM only induced their inflammatory phenotype, but not cellular senescence ( Supplemental Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molteni, R. and his colleagues found that BRAF V600E in macrophages induce hallmark immunometabolic features of trained immunity, causing activation of the AKT/mTOR signaling axis, increased glycolysis, epigenetic changes on promoters of genes encoding cytokines, and enhanced cytokine production leading to hyper-inflammatory responses [ 14 ]. Biavasco, R. and his colleagues discovered that the activation of BRAF V600E impairs HSPC function, features myeloid restricted hematopoiesis, and leads to a widespread inflammatory condition [ 15 ]. These findings reveal the cause of high inflammatory condition in ECD patient, explain the rationale for pancreatic involvement and the robust response to IFN in our case.…”
Section: Discussionmentioning
confidence: 99%